Las relaciones familiares en el rendimiento escolar de los niños y niñas del centro educativo comunitario intercultural bilingüe “Atapo Larcapamba”, de la comunidad Atapo Larcapamba de la parroquia Palmira, cantón Guamote, provincia de Chimborazo en el período 2010 - 2011. - Machado Hidalgo, Rogelio Washington (2011)
The present work analyzes the existent relationship among the Family Relationships in the development of the self-esteem for the school yield of the children and girls of the Community Educational Center Bilingual Intercultural "Atapo Larcapamba" of the community Atapo Larcapamba, parish Palmira, Canton Guamote county of Chimborazo. It was made with possibilities of to optimize and to innovate the context socio educativo, in the search of an atmosphere of respect, solidarity, cooperation and all the actors' of the pedagogic community participation in the process of teaching learning. To get the objectives of the project it was carried out a qualitative investigation, of field and action in their descriptive and explanatory levels, which were developed in four moments with their respective constituent elements: The Problem; Theoretical Marco; Methodology and the Marco Office worker. In the first stage an analysis of the community context, bibliographical revision with current authors was executed on the topic. We also exposed with clarity the personal approach according to our experience, same that made possible to sustain the investigative work. In the Theoretical Marco we assume the concepts, theoretical budgets and other elements, the obtained scientific conception, it was good us to articulate the hypothesis appropriately with their respective variables in order to facilitate a clear and coherent study that benefits to the fundamental attainment that is the improvement of the family Relationships, in the self-esteem and that the school yield of children and girls have the prospective achievements The methodology explains the applied pattern, the population or universe selected according to the thematic one detailedly, making an exhibition of the selected instruments and its operative procedure. In the gathering of data the Technique of the Survey was used applied to the authority and educational, family parents, children and girls that it facilitated us to pick up the information, at the same time that left it systematizing in order to make the referred analysis and interpretation of results. The analysis and discussion of results are exposed through squares, graphics and their corresponding interpretations, conclusions and recommendations, as well as the confirmation of the hypothesis with the help of the descriptive statistic supported in the percentage method this non alone investigation seeks to arrive until the part of the conclusions and recommendations, but the one of formulating a proposal, after the analysis made on the base of the results obtained in global form that can be presented It is an important proposal to begin a new stage of educational development, the efforts that are carried out to revert this situation will facilitate to have an educated population that can face the challenges that it imposes the current opening process and globalization of the economy appropriately. We outline solutions and the different actors' prospective achievements that conform the institutional pedagogic community; therefore, they are orientations of public character that point out the goals that should be reached to get an education of quality. To verify the knowledge, abilities and the educational actors' attitudes (students, educational and directive, family parents), the same ones that are evidenced in actions and actions that can be observed and evaluated in the contexts in those that these they are unwrapped, The educational list that the parents carry out in the breast of the home is supplemented with the action that you/they develop the educational centers; multiple technical, human, economic, social, political problems exist, etc, they determine that the educational structure is faulty and take place many failures in the human being's life, the responsibility that you/they have the parents, educators and educand in this delicate problem